Assessment of airway dimensions in skeletal Class I malocclusion patients with various vertical facial patterns: A cephalometric study in a sample of the Saudi population - Ahmed Ali Alfawzan (Wolters Kluwer Medknow Publications, 2020)
OBJECTIVE: To compare airway widths among skeletal Class I malocclusion patients with different vertical facial patterns. MATERIAL AND METHODS: A total of 103 lateral cephalograms of skeletal Class I patients (mean age of 20 ± 2.3 years) with no history of orthodontic treatment, trauma, facial syndromes, or nasopharyngeal dysfunction were included. Based on the Frankfort-mandibular plane angle measurements, the sample was divided into three groups: low-angle, high-angle, and normal-angle groups. Upper and lower pharyngeal airway widths were measured as described by McNamara. The analysis of variance test was performed to compare the means of groups. Pairwise comparisons were performed using Tukey's post-hoc test. Differences were considered statistically significant at P < 0.05. RESULTS: ANOVA showed a significant mean difference between the groups for both the upper and lower airway widths withP values of 0.011 and 0.003, respectively. Tukey Pairwise comparisons showed the upper airway width to be significantly narrower in the high-angle group compared to the normal-angle (P = 0.021) and low-angle groups (P = 0.013). Furthermore, the lower airway width in the high angle group was significantly narrower than the normal angle (P = 0.020) and low-angle groups (P = 0.017). There were no statistically significant differences between normal and low angle groups. CONCLUSIONS: The upper and lower pharyngeal widths in the Class I high-angle group were significantly narrower than those in the normal-angle and low-angle groups.